Mulberry leaf polysaccharide improves cyclophosphamide-induced growth inhibition and intestinal damage in chicks by modulating intestinal flora, enhancing immune regulation and antioxidant capacity - Cheng, Ming; Shi, Yongbin; Cheng, Yumeng; Hu, Hongjie; Liu, Song; Xu, Yanping; He, Lingzhi; Hu, Shanshan; Lu, Yujie; Chen, Fengmin; Li, Jiang; Si, Hongbin (Frontiers in Microbiology, 2024)
Polysaccharides are generally considered to have immune enhancing functions, and mulberry leaf polysaccharide is the main active substance in mulberry leaves, while there are few studies on whether mulberry leaf polysaccharide (MLP) has an effect on immunosuppression and intestinal damage caused by cyclophosphamide (CTX), we investigated whether MLP has an ameliorative effect on intestinal damage caused by CTX. A total of 210 1-day-old Mahuang cocks were selected for this experiment. Were equally divided into six groups and used to evaluate the immune effect of MLP. Our results showed that MLP significantly enhanced the growth performance of chicks and significantly elevated the secretion of cytokines (IL-1β, IL-10, IL-6, TNF-α, and IFN-γ), immunoglobulins and antioxidant enzymes in the serum of immunosuppressed chicks. It attenuated jejunal damage and elevated the expression of jejunal tight junction proteins Claudin1, Zo-1 and MUC2, which protected intestinal health. MLP activated TLR4-MyD88-NF-κB pathway and enhanced the expression of TLR4, MyD88 and NF-κB, which served to protect the intestine. 16S rDNA gene high-throughput sequencing showed that MLP increased species richness, restored CTX-induced gut microbiome imbalance, and enhanced the abundance of probiotic bacteria in the gut. MLP improves cyclophosphamide-induced growth inhibition and intestinal damage in chicks by modulating intestinal flora and enhancing immune regulation and antioxidant capacity. In conclusion, this study provides a scientific basis for MLP as an immune enhancer to regulate chick intestinal flora and protect chick intestinal mucosal damage.